Computing the Ediz eccentric connectivity index of discrete dynamic structures - Wu Hualong; Kamran Siddiqui Muhammad; Zhao Bo; Gan Jianhou; Gao Wei (Open Physics, 2017)
From the earlier studies in physical and chemical sciences, it is found that the physico-chemical characteristics of chemical compounds are internally connected with their molecular structures. As a theoretical basis, it provides a new way of thinking by analyzing the molecular structure of the compounds to understand their physical and chemical properties. In our article, we study the physico-chemical properties of certain molecular structures via computing the Ediz eccentric connectivity index from mathematical standpoint. The results we yielded mainly apply to the techniques of distance and degree computation of mathematical derivation, and the conclusions have guiding significance in physical engineering.